Concentrations of polybrominated diphenyl ethers (PBDEs) in residential dust samples from Western Australia - Stasinska, A.; Reid, Alison; Hinwood, A.; Stevenson, G.; Callan, A.; Odland, J.; Heyworth, J. (2013)
Polybrominated diphenyl ethers (PBDEs) are one of the most common types of brominated flame retardants applied to foams, plastics and textiles to prevent fires. These flame retardants are now regulated and are either banned or being voluntarily phased. However, as these chemicals are persistent humans continue to be exposed. Dust has been identified as an important source of exposure and hence residential concentrations are of interest. The aim of this paper was to determine the concentrations of PBDEs in samples of residential dust from the homes of pregnant women in Western Australia. Thirty residential dust samples were analysed for concentrations of 32 PBDE congeners. Samples were collected from urban and rural areas. PBDEs were detected in all residential dust samples with the sum of the most common PBDEs (Σ7 of BDEs 47, 99, 100, 153, 154, 183 and 209) ranging from 60.4 to 82 400 ng g−1 (median 571 ng g−1). DecaBDE makes up the highest proportion of PBDEs in residential dust, on average 66% of Σ32PBDEs. We did not find a relationship between housing characteristics nor the presence of appliances and PBDE concentrations. Dust from urban areas had significantly higher concentrations of BDE-209 and Σ32PBDEs than dust from rural areas of Western Australia (p values 0.01 and 0.03 respectively). PBDEs were present in residential dust in Western Australia at concentrations higher than reported previously in Australia. Further investigation of sources with a larger sample size is required to determine associations between PBDE concentrations and potential exposure sources and geographical regions.